Late Merge and Phases for Anti‐C‐Command Requirements. (22nd March 2018) - Abe, Jun
Abstract: In this article, I propose a unified explanation for the argument–adjunct asymmetries that have been observed regarding two seemingly unrelated anti‐c‐command requirements: (i) condition C and (ii) the anti‐c‐command requirement on argument ellipsis, observed in Abe2009 for null arguments in Japanese. I argue that these asymmetries are best explained by the mechanism of late merge of adjuncts proposed by Lebeaux (1988 ) with a derivational definition of c‐command à la Epstein (1999 ). Furthermore, I argue that the timing of late merge of adjuncts is regulated by phase theory in the way that adjuncts may be merged no later than completion of relevant operations at the phase domains they belong to.